EVALUASI KESESUAIAN LAHAN TAMBAK UDANG DI KECAMATAN CIJULANG DAN PARIGI, CIAMIS, JAWA BARAT - Syaugy, Afwan; Siregar, Vincentius P.; Arhatin, Risti Endriani (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Selection of wrong location fishponds will cause the problems, such as increasing the cost of construction, operational, and may cause environmental degradation. The purpose of this study was to evaluate the land suitability for shrimp farms considering the coastal and river border planning maps in Kecamatan Cijulang and Parigi. This study uses the Geographic Information Systems (GIS) to determine the level of compliance of existing shrimp farms in the area. The parameters taken into calculated are: land use; soil texture; soil type; land slope; distance from the river; distance from the shore; water pH, and salinity. The result of the spatial analysis was added by limiting factor coastal and river border, so the extensive shrimp farms area is 23.8 ha divided into three classes of suitability, namely very accordance (11.7 ha or 49.0%); accordance (1.0 ha or 4.3%), and not in accordance (11.1 ha or 46.6%). There are no shrimp farms in the area of conditional suitability. The existing farm in this region is almost entirely located in the area that should be a river border. In order to keep a sustainable shrimp farms management, it is needed a good cooperation between the management of the shrimp farms and the government.